Prevalence and characteristics of S-point bleeding compared to non S-point bleeding in severe epistaxis - Jeong,Hamin (2021)
Abstract Introduction Stamm's S-point is gaining importance as a bleeding focus in severe epistaxis. However, prevalence and features of S-point bleeding compared to non S-point bleeding have not been studied. Objective To investigate the characteristics of patients with S-point bleeding among those with severe epistaxis and to compare the factors involved in the treatment of epistaxis. Methods We retrospectively analyzed medical records of 268 patients admitted to the otorhinolaryngology department of Konkuk University Hospital and Chung-Ang University Hospital with epistaxis of which the bleeding focus clarified. Patients with anterior nasal bleeding (n = 129) were excluded. The study was conducted at the department of otorhinolaryngology from January 2008 to August 2019. Collected data included patients' demographic information, bleeding focus, body mass index underlying medical and sinonasal diseases, laboratory test results (initial hemoglobin, platelet count, and triglyceride level), use of anticoagulants, direction of epistaxis, initial and final treatments, and need for blood transfusion. Results The prevalence of S-point bleeding was 28.8% of non-anterior bleeding cases. Mean body mass index score was lower in the S-point group (23.41 ± 3.71) compared to the non S-point group (24.93 ± 3.97) (p = 0.039). Underweight patients tended to show a greater incidence of S-point bleeding (15.0%) than non S-point bleeding (2.0%) (p = 0.010). Incidence of anemia was higher in the S-point group (67.5%) than in the non S-point group (36.4%). Anemia (Odds ratio [OR]: 3.635; 95% confidence interval [CI]: 1.669-7.914, p = 0.001) and underweight (body mass index < 18.5, OR: 8.559, CI: 1.648-44.445, p = 0.011) were significantly associated with S-point bleeding. Conclusion Prevalence of S-point bleeding was significant, underlining the importance of examining the S-point in patients with severe epistaxis. Patients with S-point bleeding had lower body mass index scores and a higher incidence of anemia than those with non S-point bleeding.